Green synthesis and characterization of CuO/ZnO nanocomposite using Musa acuminata leaf extract for cytotoxic studies on colorectal cancer cells (HCC2998) - Wong Yee Jin; Subramaniam Hemaroopini; Shing Wong Ling; Dhanapal Anto Cordelia Tanislaus Antony; Chan Yu Bin; Aminuzzaman Mohammod; Tey Lai-Hock; Janakiraman Ashok Kumar; Kayarohanam Saminathan; Djearamane Sinouvassane (Green Processing and Synthesis)
Green synthesis has become an alternative to replace chemical synthesis in nanotechnology because of its low cost and toxicity. The synthesis of nanocomposite (NC) has attracted the attention of researchers, as its synergistic effect might enhance its effectiveness in anticancer to overcome multidrug resistance. In this study, copper oxide/zinc oxide (CuO/ZnO) NC was green synthesized from the crude extract of Musa acuminata leaves with Zn(NO3)2·6H2O and Cu(NO3)2·3H2O as precursors. CuO/ZnO NC was characterized via UV-Vis analysis with a peak detected at 365 nm with a bandgap energy of 3.43 eV. Field emission scanning electron microscopy analysis showed an agglomerated, irregular shape with a size ranging from 31.8 to 85.7 nm. X-ray diffraction analysis depicted the crystallite size of 24.78 nm with hexagonal wurtzite of ZnO and monoclinic of CuO. Fourier transform infrared spectroscopy analysis showed the presence of functional groups, including hydroxyl groups, carbonyl groups, amines, alkanes, aromatic amines, Cu–O, and Zn–O. The cytotoxic effect of CuO/ZnO NC toward the colorectal cancer cells (HCC2998) was evaluated by the MTT assay and found to be dose-dependent. The results showed a significant cell mortality at 100 µg·mL−1 CuO/ZnO NC with 45.79% cell death at 24 h. The findings of the present study suggest the potential of CuO/ZnO NC to be utilized as an anticancer agent.